Interplay of things religion, art, and presence together - Pinn, Anthony B. 1964- (Duke University Press, 2021)
"Drawing on literature along with the visual and performing arts, Anthony B. Pinn theorizes religion as a technology for interrogating human experiences understanding the ways in which things are always involved in processes of exchange and interplay."--
Keywords: Art and religion / United States; Religion and culture / United States; African American art / Social aspects; Art and race; Performance art / Social aspects / United States; RELIGION / Philosophy; SOCIAL SCIENCE / Ethnic Studies / American / African American & Black Studies